New records of Agromyzidae (Diptera) from Bulgaria - Černý, Miloš; Barták, Miroslav; Kubík, Štěpán; Vála, Miloslav (Zootaxa, 2022)
New knowledge on the distribution of leaf-miner flies (Diptera, Agromyzidae) in Bulgaria are presented in this paper. New faunistic data on 219 species are presented, of which 107 species are recorded as new for the fauna of Bulgaria. Four species are described as new to science and illustrated: Ophiomyia balcanica sp. nov., Liriomyza pirinensis sp. nov., Phytomyza bulgarica sp. nov. and Phytomyza karnarensis sp. nov. Altogether, 309 species are currently known from Bulgaria.